Virtual Distance Lessons in Secondary School Teachers Continuous Education - Auziņa, Ilze; Buliņš, Zigmunds; Lavendels, Jurijs; Šitikovs, Vjačeslavs; Šteinmans, Jurijs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper provides an overview of organization principles of interactive distance teaching as well as its implementation for continuous education course for bilingual education teachers of 6 programme’s subjects. Distance teaching sessions were organized in 10 school’s computer classes. There are considered possible solutions for interactive distance learning classes. Lessons organization, based on the server’s remote session control is described. It is arranged participating teacher survey regarding usability of applied environment and made conclusions about appropriateness of developed approach.